Consumption of bovine meat in the district of Guadalupe, San José: economic model to explain the behavior of this. Year 2017 - Brenes Granados, Cristina (2018)
An econometric model that aims to explain the demand for bovine meat for the district of Guadalupe was determined; with the purpose of providing an econometric proposal that achieves a vision about the behavior of the consumer with respect to their consumption of beef, including various factors and a location in specific time and space. Because the demand for meat is variable from one period to another, we chose to use crosssectional data, which were generated through surveys (n = 106), which were applied in this place at random. The objective of the application of personal interviews was to obtain information about the variables: consumption motivations, frequency of purchase, consumption according to frequency, consumption limitations, education, occupation, monthly income and substitute products. From the information obtained from the surveys, different econometric models were run. Finally, it was concluded that the econometric model that best suited the demand for bovine meat for the Guadalupe district was the following: Ln Q = β1 + β2lnEducation + β3lnIngress + β4Prices + β5Guits + β6Qt-1 + β7Price-1 The model presented positive signs and low probabilities, in addition the intercept was applied. In addition, it was possible to determine that not all the variables consulted in the survey worked to estimate the demand, such is the case of substitutes and occupation. The same tests were applied to autocorrelation, multicollinearity and heteroscedasticity, of which only autocorrelation was positive.